Sustainable management of freshwater resources in Ghana: an analysis of the perspectives of local residents - John Amoah-Nuamah; Emmanuel Yeboah Okyere; Kow Ansah-Mensah; Martin Maxmillian Acquah; Millicent Obeng Addai; Richard Gyamfi (Cogent Social Sciences)
This study explored the perspectives of community members on the management and ownership of freshwater resources. A mixed-method study was conducted targeting household heads, traditional leaders, and assembly members in communities surrounding the lake. Household heads (309), and 14 focus group discussions were used in the study. There were 46.9% and 29.4% of the respondents who perceived that the lake was owned by the government and the community (chiefs and the indigene) respectively. While 48.2% and 28.8% perceived the traditional authority and the government separately as the managers of the lake. The study found out that, the community perceives the Lake as their resource and hence their traditional leaders should have control over it with support from the government and other NGOs. This implies that activities carried out concerning the Lake should have the approval of people to avoid conflict and power struggles.